Association of litter size with hematology parameters of Awassi Iraqi ewes - Khalif, Ameer Talib; Al-Thuwaini, Tahreer M.; Al-Shuhaib, Mohammed Baqur S. (Journal of Kerbala for Agricultural Sciences, 2020)
Reproductive traits could affect the hematological profile of ewes. Blood parameters change in relation to the reproductive status of an animal. Therefore, this study aims to investigate the possibility of an association between the litter sizes with hematology parameters in Iraqi Awassi ewes. A total of 224 sexually mature ewes (non-pregnant, non-lactation) and healthy (124 ewes with single birth and 100 ewes with twin birth), aged between 2.5 to 5 years were included in this study. Blood samples were collected from the sheep. Samples were immediately transferred to the laboratory for a hematology examination. Results revealed to some hematological changes between ewes according to litter size. The numbers of erythrocytes, Hb and PCV% were higher in Awassi ewes with twin birth (8.106 ×106/μl), (9.863 ± 0.302) and (29.623 %) respectively than ewes with a single birth. According to the leukocyte constituents, the Awassi ewes with twin birth showed higher lymphocyte and lymphocyte % than ewes with a single birth. The highest and strongly positive correlation (P < 0.01) was recorded among litter size with RBC (r=0.315, P=0.003), PCV (r=0.310, P=0.003) and lymphocytes % (r=0.366, P=0.002). In conclusion, significant differences in hematology parameters were recorded between Awassi ewes according to the type of birth. A significant increase of RBC number, PCV and lymphocyte %, were determined in Awassi ewes with twin birth. Blood parameters can be used as good indicators of inference to a litter size of Awassi ewes.